Outcomes after combined phacoemulsification and trabecular microbypass stent implantation in controlled open‐angle glaucoma. Issue 9 (September 2016) - Seibold, Leonard K.; Gamett, Kevin M.; Kennedy, Jeffrey B.; Mulvahill, Matthew J.; Kroehl, Miranda E.; SooHoo, Jeffrey R.; Pantcheva, Mina B.; Kahook, Malik Y.
Abstract : Purpose : To study the effect of combined phacoemulsification cataract surgery and iStent (trabecular microbypass stent) implantation on intraocular pressure (IOP) and medication use in open‐angle glaucoma (OAG) patients with a low mean preoperative IOP. Setting : University of Colorado Health Eye Center, Aurora, Colorado, USA. Design : Retrospective case series. Methods : Treatment outcomes analyzed included IOP, medication use, and corrected distance visual acuity (CDVA). Treatment success was defined as a 20% or more IOP reduction or discontinuation of at least 1 medication. Results : Sixty‐four eyes of 45 patients were included in the analysis. At 1 year, the mean IOP was significantly reduced from 14.7 ± 3.2 mm Hg (SD) to 13.2 ± 2.8 mm Hg ( P < .01) and the mean medication use decreased from 1.81 ± 1.13 to 1.41 ± 1.48 ( P = .0001). The estimated IOP reduction at 1, 3, 6, and 12 months was 3.5% ( P = .23), 7.9% ( P = .04), 9.7% ( P = .01), and 12.2% ( P = .002), respectively. Treatment success at 1 year was achieved in 76.1% of patients, and 41% of patients were medication free at 1 year. The CDVA was significantly improved from 0.4 ± 0.38 logMAR at baseline to 0.17 ± 0.35 at 1 year ( P < .0001). Conclusions : Combined cataract surgery and trabecular microbypass stent implantation was statistically effective in reducing IOP and/or medication burden in OAG patients with a low preoperative IOP. During the informed surgical consent process, the physician and patient should consider the clinical benefit of modest IOP lowering and/or a decrease in medication use. Financial Disclosure : Drs. Seibold, SooHoo, Pantcheva, and Kahook have received grant support from Glaukos Corp. No other author has a financial or proprietary interest in any material or method mentioned.